VERBAL INFLECTION: A CONTRASTIVE ANALYSIS ON ENGLISH AND TURKISH - Siti - Sa'diah (Universitas Muhammadiyah Tangerang, 2018)
Abstract This study aimed to investigate differences and similarities of English and Turkish verbal inflection. It was limited on verbal inflection of the three common tenses which are present, past, and future. The data used in this study were gained from both library and field research. The field research conducted was interview to two informants having background as Turkish teachers and one informant as a learner studying Turkish. The result showed that English and Turkish verbal inflections had differences and similarities. The difference was English verbal inflections were occured in Simple Present Tense and Simple Past while Turkish verbal inflections were occured in the three tenses present which is called by Şimdiki Zaman, past which is called by Geçmiş Zaman, and future which is called by Gelecek Zaman. The other difference was on the affixes used to transform the inflection. Turkish had more affixes than English. Whereas, the similarity appeared on the rules in which the process of affix inflection depends on the subjects used. This similarity was only occured on Simple Present Tense in English in which the inflected verb refered to the subject (the third singular person). Keywords: Verbal inflection, English, Turkish, Contrastive analysis